KESEJAHTERAAN RAKYAT DAN IMPLEMENTASI KEBIJAKAN TRANSPORTASI LAUT DI JAWA BARAT - Asmawi, Awing (TEMALI : Jurnal Pembangunan Sosial, 2018)
This article discusses how public policy on transport can have a welfare impact on society. The study of marine transportation is conducted in West Java, Indonesia. This is important because the development of marine transportation services can have a very close relationship with social welfare and economic growth of a region. This study uses a case study method of activities which is the implementation of the West Java government program to its people regarding sea transportation. Interview, observation, and document analysis are used to collect data. A face-to-face interview using a questionnaire has been developed for this study. The study findings show that in addition to designing and implementing the sea transportation development plan in West Java, the marine transportation policy also involves the national government of Indonesia. All marine transportation policy is intended primarily for the welfare of the community. However, here and there-there are still shortcomings that need to be improved